The Costs of Healthcare in Prison and Custody: Systematic Review of Current Estimates and Proposed Guidelines for Future Reporting - Sridhar, Shivpriya; Cornish, Robert; Fazel, Seena (Frontiers in Psychiatry, 2018)
Aims We aimed to review prison healthcare expenditure internationally. Objectives To systematically review healthcare spending on prisoners worldwide, examine comparability between countries, and develop guidelines to improve reporting. Methods Five bibliographic indexes (International Monetary Fund, ProQuest: Statistical Abstracts of the World, PubMed, Google Scholar, and JSTOR) were searched for the costs of prison and prison healthcare, supplemented with country-specific searches for the 20 countries with the highest prison populations. Information on overall healthcare costs, their breakdown by categories, and their proportion to overall prison expenditure was extracted. PRISMA guidelines were followed. Results Prison healthcare expenditure data was identified for 10 countries, and overall operating costs were reported for 12 countries. The most commonly reported healthcare cost was for primary medical care. Healthcare costs reporting varied widely, and few countries were comparable. We developed a set of guidelines for consistent and transparent reporting of healthcare costs. Conclusions Few countries report the costs of healthcare services in prison. When reported, there is a lack of clarity and consistency as to what is included in these costs. Using the proposed reporting guidelines would enable national trends and international comparisons to be investigated, and any recommended benchmarks to be monitored.